Electroacupuncture inhibits neuronal pyroptosis in ischemic brain injury through modulating SIRT5-mediated NEK7 succinylation - Lili Ma; Meiling Zhang; Ting Chen; Limin Wang; Qilong Deng (Brain Research Bulletin)
Ischemic stroke is a leading cause of global death. The treatment of this disease can inevitably result in reperfusion, thereby triggering cerebral ischemia-reperfusion injury (IRI) and neuronal pyroptosis. Electroacupuncture derived from traditional acupuncture has been proven to have favorable effects on ameliorating brain IRI and pyroptosis. Hence, the goal of the current research was to elucidate the mechanism governing electroacupuncture in cerebral IRI. We employed middle cerebral artery occlusion (MCAO) model to induce brain IRI. Our results revealed that electroacupuncture attenuated IRI in MCAO mice by minishing brain damage and hindering neuronal pyroptosis. Strikingly, it was discovered that electroacupuncture provoked the decrease of succinylation level and enhanced expression of SIRT5. Then, we demonstrated that knockdown of SIRT5 reversed the role of electroacupuncture in cerebral infarct injury and pyroptosis. In terms of mechanism, SIRT5 impeded the succinylation modification of NEK7 at K81 site to downregulate its expression level. Eventually, overexpression of NEK7 abrogated the impacts of electroacupuncture on MCAO mice. In conclusion, electroacupuncture restrained neuronal pyroptosis after cerebral ischemia via desuccinylating NEK7 in a SIRT5-dependent way.